ANALYSIS OF NON-DESTRUCTIVE TESTING IN THE METAL STITCHING PROCESS - Saputra, Ryandi Daffa; Zariatin, Dede Lia (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2024)
This research addresses damage and cracks in the Yanmar 6N18L – EV engine block through metal stitching, a coldwelding method using pins and locks to prevent thermal and mechanical cracks. The study aims to assess crack quality post metal stitching via NDT Liquid Penetrant and hardness through NDT Hardness Testing. Economic value is also evaluated. Data is collected through field observation and experimentation, meeting ASTM 159 G3500 standards. Results indicate successful crack repair, meeting NDT Liquid Penetrant standards, and achieving a 230.6 HB average hardness with a 4.82% variance, aligning with ASTM 159 G3500's 207-255 HB range. Economically, metal stitching proves beneficial with an NPW of Rp 412,353,912, making it a preferred solution for engine block crack issues.